The Effect of Financial Literacy and Financial Technology on Student Financial Behavior with Self-Control as Mediation: A Study on Students of Private Universities in Surabaya - Amalia, Mekar Meilisa (Westscience Press, 2025)
This study examines the influence of financial literacy and financial technology on students' financial behavior, with self-control serving as a mediating variable. A quantitative research design was employed, involving 160 students from private universities in Surabaya. Data were collected using a Likert scale questionnaire (1–5) and analyzed using Structural Equation Modeling - Partial Least Squares (SEM-PLS 3). The results revealed that financial literacy significantly enhances self-control, which in turn positively influences financial behavior. Financial technology also positively impacts self-control, albeit to a lesser degree. Self-control fully mediates the relationship between financial literacy and financial behavior and partially mediates the effect of financial technology. These findings underscore the critical role of self-control in shaping responsible financial practices among students, emphasizing the need for integrated educational and technological strategies to improve financial behavior.